BENEFITS OF BREASTFEEDING AND FEEDING WITH MOTHER'S MILK FOR THE CHILD - Andreja Tekauc Golob (The Society for Children with Metabolic Disorders, 2022)
Human milk, especially mother's milk, is the optimal food for infants. Breastfed children grow and gain weight more appropriately, are less often ill and have better neurological development. The unique composition of human milk, which contains anti-infective and anti-inflammatory factors, along with skin-to-skin contact from direct breastfeeding, promotes optimal growth, protects from environmental risk factors, and promotes the development of the child's innate immune system. Human milk, compared to infant formula, also provides continued protection against acute illnesses in the first years of life. Breastfeeding has been associated with long-term benefits by reducing the risk of several chronic diseases. Extensive research confirms that many acute and chronic paediatric disorders, such as otitis media, acute diarrhoeal diseases, lower respiratory illnesses, sudden infant death syndrome, inflammatory bowel disease, childhood leukaemia, diabetes mellitus, obesity, hypertension, asthma, and atopic dermatitis, occur less frequently among children who were breastfed at an early age. In this review article, some of the benefits of breastfeeding and feeding with breast milk or human milk for the child are discussed.